Peguasaan Kosakata Bahasa Mandarin Tingkat HSK I pada Siswa Sekolah Menengah Atas - J, Yuspani Amelia; Usman, Misnawaty; Burhanuddin, Burhanuddin (Universitas Negeri Makassar, 2021)
Abstract. This research aims to describes the mastery of Mandarin language vocabulary at HSK level I of 11th grade students of SMA Dian Harapan Makassar. The method used of this research was to conduct a vocabulary mastery test which consisted three kinds of tests, that is vocabulary translation test, sentence completion test and matching characters of Hanzi with Pinyin test which analyzed using the percentage formula, The results reached 96.4% with the conclusion that mastery of Mandarin vocabulary at HSK level of 11th grade students of SMA Dian Harapan was included in the perfect category.